PENENTUAN HARGA JAGUNG DALAM KETERIKATAN MODAL PERSPEKTIF HUKUM EKONOMI SYARIAH - indah Indah; A. Kumedi Ja’far; Herlina Kurniati (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2025)
The practice of agricultural trade under a capital-binding system is still widely found in Tekad Village, Pulau Panggung District, Tanggamus Regency. In this system, farmers receive capital in the form of seeds or production supplies from middlemen; however, in return, they are obliged to sell their harvests back to the lenders at prices unilaterally determined. This situation creates an imbalance, as the prices received by farmers are lower than the market value, causing economic disadvantages and raising questions of fairness in such transactions. This study aims to examine the pricing mechanism in the sale and purchase of corn within the capital-binding system and to assess whether the practice aligns with the principles of Islamic economic law. The findings reveal that corn prices are set solely by the middlemen, averaging IDR 4,000 per kilogram, while the market price reaches IDR 4,800 per kilogram. Although some farmers accept these conditions because they feel helped by the initial capital, the practice essentially reduces their rightful profit. From the perspective of Islamic economic law, such unilateral price determination does not reflect the principles of justice and mutual consent that should underpin transactions in muamalah. Therefore, this system needs improvement to ensure greater fairness and compliance with Sharia values.